Instrumentos para evaluar el cambio de hábitos relacionados con el control de peso - Villalobos-Daniel, Victor Eduardo; Campos Nonato, Ismael; Camarillo, Gabriela; Enríquez Santamaría, Roberto (RESPYN Revista Salud Pública y Nutrición, 2012)